Edukasi Pencegahan Penularan Tuberkulosis di Desa Borisallo - Latif, Aulia Insani; Tiala, Nur Hijrah; Masahuddin, La (PT.Mantaya Idea Batara, 2023)
Tuberculosis (TB) is a hypersensitive infectious disease caused by Mycobacterium Tuberculosis. The bacteria infects the lungs (pulmonary TB), but can also infect other parts of the body (extrapulmonary TB). About 5-10% of the 1.7 billion people infected with TB will develop TB disease in their lifetime. The level of knowledge that is lacking will have an impact on increasing TB transmission and delaying the healing period or not maximizing TB treatment. Another impact of the lack of knowledge about TB is that it can lead to non-adherence during treatment. So that the success of TB treatment is largely determined by the high level of patient knowledge. This is a problem for partners, so it is important to provide counseling regarding the prevention of TB transmission. The service method is lecture/counseling, accompanied by simulations and questions and answers. This community service was held in January in Borisallo Village, Parangloe District, Gowa Regency, to be precise in the courtyard area of the Borisallo village office. The expected results are in accordance with the plan where participants are able to understand how to prevent transmission of TB disease and are enthusiastic during the counseling process.